CRITICAL ANALYSIS OF RADIOMICS IN RADIATION ONCOLOGY - Firas Ahmed Kshmiri, Waleed SulaimanAlrashidi, Assem Abdulrahman Alharbi, FerasYahyaAsiri, Taha Ali Alshatry, Abdullah MarzouqAljohani (Chelonian Research Foundation, 2023)
Radiomics could be a phenomenon in radiation oncology that provides an incredible way to move treatment forward through quantitative investigation of therapeutic pictures. This basic assessment provides an understanding of the utilization of radiology for individualized treatment arranging and result expectations. Synthesize methods, results, and conclusions of significant considerations to assess the current field of radiomics in radiation oncology. Imperatively, the discoveries highlight the relationship between radiographic marks and clinical results and uncover the potential to advance clinical procedures. In any case, challenges stay, particularly regarding repeatability and planning. Tending to these issues is fundamental to the fruitful assessment of radionics in radiation oncology. Proposals for future inquiries address these confinements to progress the integration of radiology into schedule hone and advance understanding improvement.